2017
DOI: 10.1021/acs.chemmater.7b02638
|View full text |Cite
|
Sign up to set email alerts
|

I2–II–IV–VI4 (I = Cu, Ag; II = Sr, Ba; IV = Ge, Sn; VI = S, Se): Chalcogenides for Thin-Film Photovoltaics

Abstract: Recent work has identified a non-zinc-blendetype quaternary semiconductor, Cu 2 BaSnS 4−x Se x (CBTSSe), as a promising candidate for thin-film photovoltaics (PVs). CBTSSe circumvents difficulties of competing PV materials regarding (i) toxicity (e.g., CdTe), (ii) scarcity of constituent elements (e.g., Cu(In,Ga)(S,Se) 2 /CdTe), and (iii) unavoidable antisite disordering that limits further efficiency improvement (e.g., in Cu 2 ZnSnS 4−x Se x ). In this work, we build on the CBTSSe paradigm by computationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
123
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(142 citation statements)
references
References 69 publications
18
123
1
Order By: Relevance
“…All three band alignments are expected to exist within the AEnTPbX 4 family. To facilitate rational selection of COP compounds exhibiting the three distinct behaviors, we extend the demanding hybrid spin-orbit-coupled DFT [33][34][35][36][37][38][39][40][41] calculations of Liu et al 3 with newly-predicted band alignments in the AEnTPbX 4 family with n = 1-5, X = Cl, Br, I ( Fig. S1 and Table S1, ESI †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three band alignments are expected to exist within the AEnTPbX 4 family. To facilitate rational selection of COP compounds exhibiting the three distinct behaviors, we extend the demanding hybrid spin-orbit-coupled DFT [33][34][35][36][37][38][39][40][41] calculations of Liu et al 3 with newly-predicted band alignments in the AEnTPbX 4 family with n = 1-5, X = Cl, Br, I ( Fig. S1 and Table S1, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…In traditional inorganic semiconductors with similar band gaps, we would expect this choice to systematically underestimate the fundamental gap by approximately 0.3 eV. 39…”
Section: Film Characterizationmentioning
confidence: 99%
“…As a result of copper substitution with silver, the amount of band tailing decreases indicating less structural disorder. These experiments indicate that there is a great potential in engineering the properties of CZTS-like materials and theoretical attempts are already being made to expand the materials space beyond CZTS for optoelectronic applications [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al reported the optical properties of Cu 2 BaSn(S x Se 1-x ) 4 , including the optical absorption coefficients of Cu 2 BaSnS 4 (P3 1 ) and Cu 2 BaSnSe 4 (Ama2). [76] The absorption coefficient of Cu 2 BaSnS 4 (P3 1 ) is isotropic in this region, similar to that of CZTSSe. However, the absorption coefficient of Cu 2 BaSnSe 4 with a much lower bandgap is much higher than that of Cu 2 BaSnS 4 when the spectral region is up to 2.5 eV.…”
Section: Optical Propertiesmentioning
confidence: 64%